Peran Literasi Digital dalam Mendorong Kemampuan Berpikir Siswa Sekolah Menengah Atas: Kajian Literatur Terkini - Ramadhan, Muh Rafi Nur (-, 2025)
Digital literacy has become an essential competency in the 21st century, particularly for senior high school students. Critical thinking is part of higher-order thinking skills that are crucial for filtering digital information. This study aims to review recent research findings on the relationship between digital literacy and students’ thinking abilities at the senior high school level. The method used is a systematic literature review of scientific articles published between 2019 and 2024. The findings indicate that digital literacy significantly contributes to shaping students’ thinking, especially in terms of information analysis, evaluation of online content, and problem-solving. Digital literacy also plays a role in fostering students’ reflective attitudes when dealing with disinformation. This study recommends strengthening digital literacy programs in schools to enhance students' overall thinking quality.